Optimization on Fc for Improvement of Stability and Aggregation Resistance - Chen, Xiaobo; Zeng, Fang; Huang, Tao; Cheng, Liang; Liu, Huan; Gong, Rui (Current Pharmaceutical Biotechnology, 2016)
Fc-based therapeutics including therapeutic full-size monoclonal antibodies (mAbs) and Fcfusion proteins represent fastest-growing market in biopharmaceutical industrial. However, one major challenge during development of Fc-based therapeutics is how to maintain their efficacy in clinic use. Many factors may lead to failure in final marketing. For example, the stability and aggregation resistance might not be high enough for bearing the disadvantages during fermentation, purification, formulation, storage, shipment and other steps in manufacture and sale. Low stability and high aggregation tendency lead to decreased bioactivity and increased risk of immunogenicity resulting in serious side effect. Because Fc is one of the major parts in monoclonal antibodies and Fc-fusion proteins, engineering of Fc to increase its stability and reduce or eliminate aggregation due to incorrect association are of great importance and could further extend the potential of Fc-based therapeutics. Lots of studies focus on Fc optimization for better physical and chemical characteristics and function by structured-based computer-aid rational design, high-throughput screening expression system selection and other methods. The identification of optimized Fc mutants increases the clinic potential of currently existed therapeutics mAbs and Fc-fusion proteins, and accelerates the development of new Fc-based therapeutics. Here we provide an overview of the related field, and discuss recent advances and future directions in optimization of Fc-based therapeutics with modified stability and aggregation resistance.
Keywords: stability